Early Childhood Pre-service Teachers’ Awareness on Digital Game Addiction - Karademir Coşkun, Tuğra; Filiz, Ozan (Addicta: The Turkish Journal on Addictions, 2019)
This study examines the factors that lead to digital game addiction in children based on the perspectives of early childhood pre-service teachers and has defined the relationships among the factors. For this purpose, basic interpretive research has been used as the research design. The study’s participants consist of 55 early childhood pre-service teachers studying in the 2nd grade of Early Childhood Education Department in a public university during the 2017-2018 school year. The data have been collected using a semi-structured interview form developed by the researchers. Content analysis has been used to analyze the data. The findings reveal that family, children, environment, and games are the main themes that cause digital game addiction. Being an improper role model, improper technology use, wrong roles assigned to technology, work intensity, lack of knowledge, lack of control, apathy, and doing everything the child wants are the sub-themes for family. The sub-themes for children are finding an imaginary world, age characteristics, enjoyment, struggling to belong, lack of socialization, and lack of self-confidence. Bad urbanization, insecurity in the streets, and the digitalized world are sub-themes for environment, while the theme of games has two sub-themes: a game’s attractiveness and physiological effect.To
Keywords: Game addiction; Early childhood; Pre-service teachers; Digital games •Addiction factors